2014
DOI: 10.1089/vbz.2013.1378
|View full text |Cite
|
Sign up to set email alerts
|

Infections byLeptospira interrogans, Seoul Virus, andBartonellaspp. Among Norway Rats (Rattus norvegicus) from the Urban Slum Environment in Brazil

Abstract: Norway rats (Rattus norvegicus) are reservoir hosts for zoonotic pathogens that cause significant morbidity and mortality in humans. Studies evaluating the prevalence of zoonotic pathogens in tropical Norway rat populations are rare, and data on co-infection with multiple pathogens are nonexistent. Herein, we describe the prevalence of leptospiral carriage, Seoul virus (SEOV), and Bartonella spp. infection independently, in addition to the rates of co-infection among urban, slum-dwelling Norway rats in Salvado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
123
6
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 39 publications
10
123
6
2
Order By: Relevance
“…The frequency of seropositive rats in both zoos was lower than that previously described in Baltimore (32%) 12 , Copenhagen (94%) 8 , and Salvador (63.1%) 13 . This unexpected outcome might be explained by the limited sample size in this study.…”
contrasting
confidence: 71%
See 2 more Smart Citations
“…The frequency of seropositive rats in both zoos was lower than that previously described in Baltimore (32%) 12 , Copenhagen (94%) 8 , and Salvador (63.1%) 13 . This unexpected outcome might be explained by the limited sample size in this study.…”
contrasting
confidence: 71%
“…seropositivity between sexes (p = 0.211) or sampling locations (p = 0.645). Although a higher prevalence in females was found in a previous study 12 , no such difference was expected, as the risk of exposure is similar for both sexes 2,8,13 .…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…have been conducted in Brazil: one in synanthropic rodents (Rattus norvegicus) in the state of Bahia (northeastern Brazil) and one in wild rodents in the state of Mato Grosso do Sul (midwestern Brazil). These studies reported the first isolation of B. queenslandensis (5/26) and B. tribocorum (1/26) in synanthropic rodents (20) and the first detection of Bartonella vinsonii subsp. arupensis in wild rodents (21).…”
mentioning
confidence: 99%
“…A few major cities in Brazil (São Paulo, Salvador, Recife and Curitiba) have shifted the focus of their interventions from rodenticide-focused pest control to a more holistic approach of integrated interventions (e.g., education, poisoning and environmental modifications). Nevertheless, the lack of knowledge regarding the social and ecological determinants influencing rodent infestation in these settings has been a barrier to implement more effective rodent control 13,14,15,16 .…”
Section: Introductionmentioning
confidence: 99%